Using the limit definition, how do you find the derivative of # f ( x) = x^4#?

Answer 1

#f' (x)=4x^3#

Given #f (x)=x^4#
Let #y=x^4#
replace #y# with #y+Delta y# and #x# with #x+Delta x#
#y=x^4#
#y+Delta y=(x+Delta x)^4#
#y+Delta y=x^4+4*x^3(Delta x)+6*x^2(Delta x)^2+4x(Delta x)^3+(Delta x)^4#
Subtract #y# from both sides
#y+Delta ycolor(red)(-y)=x^4+4*x^3(Delta x)+6*x^2(Delta x)^2+4x(Delta x)^3+(Delta x)^4color(red)(-x^4)#
#Delta y=4*x^3(Delta x)+6*x^2(Delta x)^2+4x(Delta x)^3+(Delta x)^4#
Divide both sides by #Delta x#
#(Delta y)/(Delta x)=(4*x^3(Delta x)+6*x^2(Delta x)^2+4x(Delta x)^3+(Delta x)^4)/(Delta x)#
#(Delta y)/(Delta x)=4*x^3+6*x^2(Delta x)+4x(Delta x)^2+(Delta x)^3#
Take now the #color(blue)("LIMIT")# of # (Delta y)/(Delta x)# as #Delta x rarr 0 #
#color(blue)(dy/dx=lim_(Deltax rarr 0)(Delta y)/(Delta x)=color(blue)(lim_(Delta xrarr 0)(4*x^3+6*x^2(Delta x)+4x(Delta x)^2+(Delta x)^3)=4x^3)#

God bless....I hope the explanation is useful.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Here is an alternative using one form of the limit definition.

I am using the limit definition in the form

#f'(a) = lim_(xrarra)(f(x)-f(a))/(x-a)#
For #f(x)=x^4#, we get
#f'(a) = lim_(xrarra)(x^4-a^4)/(x-a)# #" "#
(This has form #0/0#, so #x-a# is a factor of the numerator)
# = lim_(xrarra)((x-a)(x^3+x^2a+xa^2+a^3))/(x-a)# #" "# (form #0/0#)
# = lim_(xrarra)(x^3+x^2a+xa^2+a^3)#
# = (a)^3+(a)^2a+(a)a^2+a^3#
# = 4a^3#
Since #f'(a) = 4a^3#, we get
#f'(x) = 4x^3#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the derivative of the function (f(x) = x^4) using the limit definition of the derivative, we use the formula:

[f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h}]

Substitute (f(x) = x^4) into this formula:

[f'(x) = \lim_{h \to 0} \frac{(x + h)^4 - x^4}{h}]

Expand ((x + h)^4):

[(x + h)^4 = x^4 + 4x^3h + 6x^2h^2 + 4xh^3 + h^4]

Substitute this expansion into the formula:

[f'(x) = \lim_{h \to 0} \frac{(x^4 + 4x^3h + 6x^2h^2 + 4xh^3 + h^4) - x^4}{h}]

Cancel (x^4) terms:

[f'(x) = \lim_{h \to 0} \frac{4x^3h + 6x^2h^2 + 4xh^3 + h^4}{h}]

Factor out (h) from the numerator:

[f'(x) = \lim_{h \to 0} \frac{h(4x^3 + 6x^2h + 4xh^2 + h^3)}{h}]

Cancel (h) from the numerator and denominator:

[f'(x) = \lim_{h \to 0} (4x^3 + 6x^2h + 4xh^2 + h^3)]

Now, take the limit as (h) approaches 0:

[f'(x) = 4x^3]

Therefore, the derivative of the function (f(x) = x^4) is (f'(x) = 4x^3).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7